2008
DOI: 10.1017/s0033291708003607
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of admission to acute psychiatric in-patient facilities: a national survey in Italy

Abstract: In a mixed, public-private psychiatric care system, like the Italian one, public and private facilities admit patients with widely different clinical characteristics and needs. Family support represents an important resource for most patients, and interventions specifically addressed to relieving family burden are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 35 publications
7
31
0
3
Order By: Relevance
“…With respect to disability it can also be observed that there is a greater percentage of people that belong to the dependent group (DeC or DeH) who obtain the highest disability scores in all. In the occupational DAS it can be seen that the group of independents does not have disability problems in this area; nevertheless, more than 50% of people who belong to the other three groups do.With respect to the family DAS, we observe that the sample of residential patients have severe family problems, and this may be the reason why they are admitted to hospital or residential services 28 . The results provide evidence that dependent people in the sample are those who present the greatest problems in psychosocial functioning, and those people in the group of independents stand out due to their level of integration in community social activities.…”
Section: Discussionmentioning
confidence: 91%
“…With respect to disability it can also be observed that there is a greater percentage of people that belong to the dependent group (DeC or DeH) who obtain the highest disability scores in all. In the occupational DAS it can be seen that the group of independents does not have disability problems in this area; nevertheless, more than 50% of people who belong to the other three groups do.With respect to the family DAS, we observe that the sample of residential patients have severe family problems, and this may be the reason why they are admitted to hospital or residential services 28 . The results provide evidence that dependent people in the sample are those who present the greatest problems in psychosocial functioning, and those people in the group of independents stand out due to their level of integration in community social activities.…”
Section: Discussionmentioning
confidence: 91%
“…A heterogeneidade entre as reformas na assistên-cia conduzidas nos diversos países dificulta a comparação objetiva de estratégias [12][13][14][15][16][17] . Nesse contexto, a necessidade de produzir dados relevantes para a avaliação das mudanças nos serviços de saúde mental já foi apontada por outros autores 18,19 e constitui a essência do presente artigo.…”
Section: Discussionunclassified
“…In other samples including first episode psychotic patients, the literature indicates a diagnosis of schizophrenia as a risk factor for compulsory hospitalization 36 . In a recent national survey conducted in Italy about patterns of admission to acute psychiatric in-patient facilities, non affective psychoses accounted for a large extent of compulsory admissions 37 . Sociodemographic characteristics, a positive family history of any psychiatric illness, and any non-positive symptoms, were all not significantly associated with a discharge diagnosis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%